2019
DOI: 10.1002/jbmr.3734
|View full text |Cite
|
Sign up to set email alerts
|

Gaucher Disease in Bone: From Pathophysiology to Practice

Abstract: Gaucher disease (GD) is a rare, genetic lysosomal disorder leading to lipid accumulation and dysfunction in multiple organs. Involvement of the skeleton is one of the most prevalent aspects of GD and a major cause of pain, disability, and reduced quality of life. Uniform recommendations for contemporary evaluation and management are needed. To develop practical clinical recommendations, an international group of experienced physicians conducted a comprehensive review of 20 years’ of the literature, defining te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
81
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 115 publications
3
81
0
7
Order By: Relevance
“…Two observations, already accepted in Gaucher research, were also confirmed in this machine-learning study: first, the fact that spleen-removal patients have a higher risk of presenting more serious and extensive bone disease; second, our observation that almost all patients with new bone crisis – despite having received long-term ERT – had previous bone lesions, which remind us that the most feared complication in GD1 are not solved merely by starting ERT. These two facts confirm previous reports and provide validity of our analysis [ 42 , 45 47 ]. In addition, genotypes different from homozygous NM_000175.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Two observations, already accepted in Gaucher research, were also confirmed in this machine-learning study: first, the fact that spleen-removal patients have a higher risk of presenting more serious and extensive bone disease; second, our observation that almost all patients with new bone crisis – despite having received long-term ERT – had previous bone lesions, which remind us that the most feared complication in GD1 are not solved merely by starting ERT. These two facts confirm previous reports and provide validity of our analysis [ 42 , 45 47 ]. In addition, genotypes different from homozygous NM_000175.…”
Section: Discussionsupporting
confidence: 93%
“…This study is the first attempt to establish a correlation network among different biochemical and clinical characteristics in a national-base cohort. We have aimed to analyse diagnostic data and to relate them with long-term complications as bone crises, development of neoplasia or PD, which are the most common and disabling complications [ 41 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the rst attempt to establish a correlation network among different biochemical and clinical characteristics in a national-base cohort. We have aimed to analyse diagnostic data and to relate them with long-term complications as bone crises, development of neoplasia or PD, which are the most common and disabling complications (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…It is a priority to identify accurate risk factors of bone crisis to improve treatment dosage and to avoid this complication. The standard biomarkers related to GD (ChT activity, CCL18/PARC and GluSph concentrations) have been discarded as risk factors for bone complication (50,51) even though their concentration will be increased during bone crisis, due to the acute in ammatory event (45,49). This reminds us of the importance to continue searching for other biomarkers.…”
Section: Discussionmentioning
confidence: 99%